GOOD CORPORATE GOVERNANCE AND TAX AVOIDANCE TO COST OF DEBT WITH GROWTH OPPORTUNITYAS MODERATING (Empirical Study on Manufacturing Company and Finance Service Listed in IDX 2015-2019) - Sugiyanto Sugiyanto; Fitri Dwi Febrianti; Suripto Suripto (The Accounting Journal of Binaniaga, 2020)
Principles of good corporate governance can strengthen the relationship between the effect of Tax Avoidance, the Board of Commissioners and Managerial Ownership of the Cost of Debt on manufacturing companies listed on the Indonesia Stock Exchange (IDX). The hypothesis in the study uses the Eviews tool, tested 3 models 1) approach before using partial moderating (2) approach before using simultaneous moderating (3) The moderating growth opportunity.Samples consist of purposive sampling model with multiple linear regression analysis methods. The data used is the company's financial statements for 2015-2019. Research was taken from 28 selected manufacturing companies listed on the Indonesia Stock Exchange (IDX) and found samples 140 financialstatements.The results of observation were obtained partially by Tax Avoidance has a significant effect on the Cost of Debt, the Board of Commissioners has not a significant effect on the Cost of Debt, and Managerial Ownership has a significant effect on Cost of Debt. While simultaneously Tax Avoidance, Board of Commissioners, and Managerial Ownership influence the Cost of Debt. The moderating of growth opportunity strengthens the relationship between Good Corporate Governance and positive coefficient on the cost of debt, strengthened by the Leverage and Size control variables